STUDY LITERATURE: BIOPSYCHOLOGICAL REVIEW IN IMPROVING CHILDREN'S CONCENTRATION - Salim, Agus; Suwarta, Nyoman; Mado, Arifin (Antis Publisher, 2024)
Concentration is very important and needed for children in following the learning process. learning concentration can be seen from an increase in the presence of neurotransmitters. Neurotransmitters function as chemical messengers that play an important role in information processing throughout the nervous system. The purpose of this research is to describe the Literature Study: A Biopsychological Review in Improving Children's Concentration. This research uses library research with a qualitative descriptive approach. Based on the results of the review of 25 (twenty-five) journals examined by the author, there are various effectiveness of neurotransmitter performance involved in various brain functions, such as sleep, mood, emotion, attention, and learning and memory. The conclusions of this study include: 1) Neurotransmitter metabolites include biogenic amines (catecholamines norepinephrine, epinephrine, and dopamine and serotonin) and amino acids (glycine, glutamate, and γ-aminobutyric acid [GABA]), 2) Serotonin is useful for neurotransmitters and concentration, 3) Neurotransmitters including acetylcholine play an important role in the development of brain nerve structures and cells. Acetylcholine (ACh) is the first identified cholinergic neurotransmitter, and changes in its content can fully reflect the growth and development of the body as well as learning ability and memory, 4) Students who are able to concentrate during lessons will have higher memory and easily understand what is learned and 5) The researcher suggests that future studies examine the effect of one of the various types of neurotransmitters on children's concentration and motivation to learn.